FRESH : Recipes For Enjoying Ingredients At Their Peak (Better homes & gardens fresh, 2013)
"The best of fresh, seasonal cooking from Better Homes and GardensAs the farm-to-table movement grows, more people every day are choosing to cook healthier meals using fresh local foods. Better Homes and Gardens Fresh presents 300 appealing recipes for seasonal produce. No matter where you live, this book shows you how to prepare simple, delicious meals using fresh ingredients at their peak. Enjoy recipes for snacks and appetizers, breakfast, salads, soups, casseroles, main dishes, meatless meals, sides, and desserts. In addition, one-pan recipes help you keep it simple, as well as fresh. The book also includes a beautifully illustrated produce guide to help you pick and prepare food at its peak. Features 300 recipes for fresh, flavorful meals every day Illustrated with hundreds of full-color food photographs and 65 photos in the produce guide Includes a section of menus to help you craft a wide variety of meals From coast to coast, people are discovering just how delicious and rewarding it is to cook and eat local foods. With Better Homes and Gardens Fresh, you'll find a wealth of recipes and resources to help you eat fresh, seasonal meals every day"--